Perfil enzimático e potencial biotecnológico de fungos isolados de jardins das formigas cortadeiras - Costa, Rafael Rodrigues da [UNESP] (2014)
Leaf-cutting ants harbor in their nests a complex microbial consortium. These insects maintain a mutualistic interaction with fungi cultured for food. In addition to the fungal partner, alien fungi are also present in leafcutter nests, but little is known about the ecological role they play in the interaction. From a pool of 235 fungal isolates kept at the UNESP-Microbial Resource Center, we characterize the enzymatic profile of these microorganisms derived from nests of Atta sexdens rubropilosa (dicot-cutting ant) and Atta capiguara (grass-cutting ant). An adapted high-throughput screening approach was used to assess the production of cellulase, pectate lyase, polygalacturonase and xylanase. Regarding the total number of isolates, 94% (n = 220) were positive for at least one of the tested enzymes. Cellulase, polymetylgalacturonase, polygalacturonase and xylanase were produced by 72, 71, 53 and 33% of the total isolates, respectively. No fungi produced amylase. According to the correspondence analysis, isolates belonging to A. sexdens rubropilosa and A. capiguara nests had an enzymatic profile related to the production of polymetylgalacturonase and xylanases, respectively. Such difference is likely related to the type of plant substrate used by the ants to nourish their fungal cultivar. The fungi Penicillium citrinum and Fusarium solani were selected among the 235 isolates and used in growth assays of the ant cultivar. When the mutualistic fungus was grown in the hydrolysis products of plant polysaccharides generated by P. citrinum and F. solani, we observed a significant growth of the ant fungus in the hydrolysis products of carboxymethylcellulose and xylan. Such results support the hypothesis that microorganisms found in nests of leaf-cutting ants may assist in the degradation of the plant material present in the nest, with consequent release of nutrients to the fungal mutualist. In addition to the ecological approach, this study also ...